Corporate governance mechanisms, accrual and real earnings management in Malaysia: the moderating role of family ownership and whistle-blowing policy - Al-Absy, Mujeeb Saif Mohsen (2019)
This study investigates the relationship between the board of directors (BOD) and the audit committee (AC) mechanisms and earnings management (EM). Furthermore, it examines the moderating effect of family ownership and the whistle-blowing policy on the relationship. The study sample involves 864 Malaysian firm-year observations, with the lowest average of return on assets for the period of 2013 to 2015. Jones and Roychowdhury Models were used to measure the accrual earnings management (AEM) and real earnings management (REM). This study reveals that board chairman’s tenure, women on the board, board chairman’s duality (board chairman is also the AC chairman) and AC chairman’s accounting expertise reduce AEM. However, board ethnic diversity, AC independence, board chairman as an ordinary member of the AC, AC accounting expertise and AC chairman’s multiple directorships increase AEM. Regarding REM, the results show that women on the board, board ethnic diversity and board chairman’s duality reduce REM. However, board independence, board chairman as ordinary member in the AC, AC chairman’s accounting expertise and women in the AC increase REM. Within the interaction effect of family ownership, corporate governance (CG) mechanisms do not have much of a role in mitigating AEM and REM. However, family ownership positively moderates the relationship between some CG mechanisms and EM, specifically chairman’s tenure (against AEM) and board ethnic diversity and AC chairman’s multiple directorships (against REM). Within the interaction effect of the whistle-blowing policy, there is a negative relationship between board ethnic diversity and board chairman’s duality with AEM and board ethnic diversity and AC independence with REM. This study alerts policymakers to re-evaluate and enhance the possibility of applying the current Code of CG in firms, in particular, those firms with family members on the board or the whistle-blowing policy.